A taxonomic revision of Stanjehughesia (Chaetosphaeriaceae, Sordariomycetes), with a novel species S. kaohsiungensis from Taiwan - Hsieh, Sung-Yuan; Goh, Teik-Khiang; Kuo, Chang-Hsin (Phytotaxa, 2021)
Stanjehughesia kaohsiungensis sp. nov. is described from decaying wood submerged in freshwater streams from Taoyuan District, Kaohsiung City, Taiwan. The phylogenetic relationship between Stanjehughesia species was sought among representative taxa from related fungal lineages within Sordariomycetes using LSU sequence data. Molecular data revealed the phylogenetic placement of S. kaohsiungensis is within Chaetosphaeriaceae and distinct from Sporidesmiaceae. While the genus is polyphyletic, a synopsis of morphological characters and a taxonomic key for Stanjehughesia species are provided to ease identification.